Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.73.105.1984
|View full text |Cite
|
Sign up to set email alerts
|

Site 522

Abstract: Principal results: Holes 522, 522A, 522B-1. Recovered a complete magnetostratigraphic record for the sedimentary sequence from Quaternary to upper Eocene, or Chron C-16-R, Nannofossil Zone 20, and Foraminifer Zone CP 15b with the exception of the middle and late middle Miocene. The correlation between the magnetostratigraphy and seafloor anomalies is good for the Oligocene and upper Eocene section. The dissolution of the Paleogene fossils is moderate or slight. One of us (K.H.) believes the site should be reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The paleo‐depth of this site is approximately 3,000 m (Tauxe et al., 1983), which is above the temporal paleo‐CCD in the South Atlantic at approximately 4,200 m (Dutkiewicz & Müller, 2021). The sediments consist mainly of calcareous nannofossil ooze with a small amount of clay and foraminifera shells (Hsü et al., 1984). Many studies in this region have reported little to no effect of dissolution on carbonate content (Hartl et al., 1995; Liebrand et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paleo‐depth of this site is approximately 3,000 m (Tauxe et al., 1983), which is above the temporal paleo‐CCD in the South Atlantic at approximately 4,200 m (Dutkiewicz & Müller, 2021). The sediments consist mainly of calcareous nannofossil ooze with a small amount of clay and foraminifera shells (Hsü et al., 1984). Many studies in this region have reported little to no effect of dissolution on carbonate content (Hartl et al., 1995; Liebrand et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…DSDP Site 522 (26°6.843ʹS, 05°7.748ʹE) is located in the eastern part of the South Atlantic Gyre, in the middle of the Angola Basin, with a modern water depth of 4,441 m (Figure 1) (Hsü et al., 1984). The paleo‐depth of this site is approximately 3,000 m (Tauxe et al., 1983), which is above the temporal paleo‐CCD in the South Atlantic at approximately 4,200 m (Dutkiewicz & Müller, 2021).…”
Section: Methodsmentioning
confidence: 99%